Motive des Ausbruchs und des Aufbruchs in den Hörspielen Ingeborg Bachmanns - Kłańska, Maria (Studia Germanica Posnaniensia, 2017)
Bachman wrote only three radio plays, all of them in the fifties of the XXth century. In spite of different settings, all of them have the same topic: escape from society (either into dream or to an island or to the isolation of a couple wishing to live only for love) and utopia. In the first and third play the male protagonists fail however, unable to give up their bourgeois lives. In the third play the female protagonist is a victim of her ability to love without restrictions. This locates The Good God of Manhattan close to the feminist prose of Bachmanns later years. In the second radio play, The Cikadas, the existence on an island separated from society is judged in the negative. All attempts to win utopian happiness end with defeat; although they are valued differently, they show that in spite of all efforts mankind is not able to reach the ideal of truth and love.